Definition of footstrike pattern during running based on strike index - Mann, R.; Urhausen, A.; Meijer, K.; Statham, A.; Brunner, R.; Gette, P.; Theisen, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It has been suggested that running style, classified as rear-foot (RFS), mid-foot (MFS) or forefoot (FFS) strike, is closely related to the risk of running-related injury occurrence (1). Foot strike pattern during running is by definition determined by the initial foot contact angle (CA) with respect to the ground. It can also be assessed using strike index (SI), the initial point of contact on the foot sole with the ground (2). Previous definitions are arbitrary, with SI values up to 33% taken as a RFS, between 33 and 66% as a MFS and above 66% as a FFS (2).The aim of this study was to provide a clear definition of running style based on the relationship between SI and the initial foot contact angle (CA). Methods: A pressure-sensitive insole, the Runalyser (by TNO Eindhoven, The Netherlands) was used to record pressure data (247 Hz) in 11 participants on a treadmill, each instructed to run in the following conditions: warm-up, FFS, MFS and RFS. SI was determined for each condition from 30-s Runalyser acquisitions and expressed as a percentage of total foot sole length. Active markers were placed at the heel and lateral metatarsophalangeal joint of the right shoe. A high-speed (200 Hz) motion analysis system (CODAmotion, Charnwood Dynamics, UK) was used to calculate the CA of the sole of the running shoe with the surface of the treadmill in the sagittal plane. Average SI and CA were calculated on >30 steps during each condition and analysed in a least squares linear regression with SI as the dependent variable. Results: SI during warm-up varied between 22.5 and 32.3%. SI values across the different running styles ranged between 20.7 and 65.5%, while CA ranged between 32 and -23°. The two variables had a strong (R2=0.83) linear relationship: SI(%)=-0.8.CA(°)+43.2. The 95% confidence interval of the y-intercept was [40.7, 45.6]. Discussion: This study provides a rationale for foot strike pattern definition based on the relationship between SI and CA. The 95% confidence interval of the y-intercept provides the boundaries to define MFS (0° CA), the SI values below and above defining RFS and FFS, respectively. This definition allows for the relationship between running style and injury occurrence to be studied in a large cohort using the Runalyser.